Sosialisasi Penggunaan Media Pembelajaran Amplop Bergambar dalam Meningkatkan Kemampuan Kognitif Siswa MIS YPII Tanjung Pura - Tuti Rezeki Awaliyah Siregar; Enda Lovita Pandiangan; Fitri Rahmadani; Rahma Khairani; Risky Ramadhanty (Pusat Riset dan Inovasi Nasional, 2022)
This community service aims to develop and increase teachers' awareness of the importance of using learning media in the classroom learning process. This activity was carried out on Thursday, 29 September 2022 at MIS YPII Tanjung Pura, Langkat Regency. The benefit of implementing this activity is to increase educators' knowledge about various variations of learning media, one of which is picture envelope learning media as well as improving students' cognitive abilities and learning outcomes.